KKN Tematik Ekoteologi dan Pertanahan untuk Pemberdayaan Masyarakat Desa Linggoasri Kecamatan Kajen Kabupaten Pekalongan - Fitri Virdha Amelia; Afif Firdaus; Nisa Fauziah; Lyta Melly Yani; Indriyani Pratiwi; Nazila P. I. Berlian; Ade Herlina; Hikmatul Lely; Yanuar Ilham Pangestu; Adinda Ramadhan (Universitas Methodist Indonesia, 2025)
Thematic KKN on Ecotheology and Land Management in Linggoasri Village, Kajen Subdistrict, Pekalongan Regency aims to improve the community's capacity in environmental management, land management, and sustainable local economic development. This activity integrates eco-theology and land management and implements additional programs such as the Digital Smart Village and the development of Jaling Coffee products. The implementation method uses a participatory, collaborative, and educational approach, with the subjects of service including students, village officials, and the local community. The results of the activity show success in assisting with waqf land certification, waste bank management, fertilizer production from coffee husks, planting 1,000 coffee seedlings, managing the Digital Smart Village, and producing and marketing Jaling Coffee, which has had an impact on increasing legal awareness, environmental management, digital literacy, and the economic welfare of the community. It is hoped that these activities can strengthen local capacity, encourage active community participation, and support sustainable, independent, and prosperous village development, while also serving as a means of contextual learning for students.